2018
DOI: 10.1002/lom3.10265
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic validation of species‐specific protocols for metal subcellular fractionation in freshwater animals

Abstract: The use of fractionation protocols to determine metal subcellular distribution in aquatic organisms has gained much interest over the last 15 yr, however, accurate separations among the different components of cells are challenging. Subcellular fractions separated with such an approach are operationally defined and a potentially significant difference can exist between anticipated and resulting fractions. This study customizes and validates subcellular partitioning protocols, for three different freshwater org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 53 publications
(108 reference statements)
3
20
1
Order By: Relevance
“…The mean (±SD) recovery values of Y were 90 ± 11% ( n = 12) for D. magna , 70.0 ± 0.1% ( n = 12) for C. riparius, and 87 ± 22% ( n = 9) for O. mykiss . Note that it was assumed by Cardon et al 16 that around 25% of C. riparius samples were probably not efficiently homogenized with the subcellular fractionation procedure performed on this species. It could explain why we obtained lower recovery values for C. riparius .…”
Section: Methodsmentioning
confidence: 99%
“…The mean (±SD) recovery values of Y were 90 ± 11% ( n = 12) for D. magna , 70.0 ± 0.1% ( n = 12) for C. riparius, and 87 ± 22% ( n = 9) for O. mykiss . Note that it was assumed by Cardon et al 16 that around 25% of C. riparius samples were probably not efficiently homogenized with the subcellular fractionation procedure performed on this species. It could explain why we obtained lower recovery values for C. riparius .…”
Section: Methodsmentioning
confidence: 99%
“…This overlap could explain the 30% APHO activity found in the mitochondria in protocol # III, where a centrifugation force of 25,000 × g was used to pellet mitochondria. In a recent study of rainbow trout, Cardon et al (2018) also suggested that lysosomes and mitochondria could be combined in the same fraction.…”
Section: Fraction Separationmentioning
confidence: 98%
“…Complete subcellular fractionation protocols. It has been recently observed in the literature that a subcellular protocol that works for on species or organ does not necessarily fit for another (Rosabal et al 2014;Cardon et al 2018;Urien et al 2018a;Khadra et al 2019). Consequently, in the present study we chose to test different tools (Potter-Elvehjem tissue grinder, cordless motor mixer, sonication, etc.)…”
Section: Effect Of a Two-step Homogenization Protocolmentioning
confidence: 99%
See 2 more Smart Citations